(untitled) (Eurasian Research Bulletin, 2022)
Linguoculturology as a special field of science has given rise to a number of productive concepts in modern linguistics: lingvoculturema, cultural language, cultural text, cultural concept, subculture, linguocultural paradigm, cultural universality, cultural potential, cultural heritage, cultural traditions, cultural process, cultural process instructions, etc. In this article researchers discussed some points of linguoculturology, especially, linguocultural aspects of texts in the process of translation.